Pengaruh Sistem Informasi Keuangan, Partisipasi Anggaran serta Sikap Perilaku Aparat terhadap Kinerja Keuangan Daerah di Provinsi Sulawesi Utara - Manaroinsong, Johny (Jurnal Aplikasi Manajemen, 2014)
This study uses quantitative approach in which focus on explanatory survey method. The population is chiefs of Sulawesi Utara Province and UPTD, they are top manager, middle manager, and top manager as persons who have responsibility and finance manager. The sample is taken using multistage sampling. Based on the consideration, therefore the sample includes 273 chiefs, in which the sample is taken from random sampling. The data collection is using questionnaire and using Likert model scale. The analysis technique that is used in order to analyze the relationship between each factor is the analysis of statistic inferential, in which focus on the econometric equation model with multiple regression. The result of the study shows that: 1) Finance information system has directly influence but does not have significance toward region finance performance. (2) The participation in making a budget plan has directly influence and significant toward region finance performance. ThereTherefore, the participation in making a budget plan gives a directly significant role towards region finance performance on SKPD at Sulawesi Utara Province. (3) Apparatus's attitude and behavior has negative influence on region finance performance, even though it does not have significance towards region finance performance. The conclusion is that finance inforinformation system in region does not give directly and strongly role towards region finance performance on SKPD at Sulawesi Utara Province.